PENGGUNAAN PENDEKATAN MATEMATIKA REALISTIK UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PELAJARAN MATEMATIKA SISWA KELAS II SEKOLAH DASAR - Amalia, Lika Suci; Widyawati, Ine; Supriati, Nelis (COLLASE (Creative of Learning Students Elementary Education), 2019)
The purpose of this study was to determine student learning outcomes in thematic mathematics learning before and after applying a realistic mathematical approach and to determine its improvement. The method to be used in this study is the Quasi Experiment method. The independent variable is learning mathematics using a realistic mathematical approach. While the dependent variable is student learning outcomes in mathematics. The type of data used is quantitative data in the form of test scores on student learning outcomes and qualitative results from observation of learning activities using realistic mathematical approaches. The population in this study were grade 2 elementary school students in Bandung in the academic year 2018/2019.Posttest results, obtained the significance value of the control class 0.001 (data not normally distributed) and experimental class 0.173 (data are normally distributed). Significance value For the average difference test / Maan Whitney is 0.731, the posttest score of the experimental class students is significantly better than the control class. Significance value N gain 0.002 control class and the significance value of the experimental class 0.047 means that the two classes are not normally distributed. Obtained a significance value of 0.634, because a one-party test is obtained, 0.634 / 2 = 0.317. This value is> 0.05 so H0 is rejected. So, increasing the ability to understand concepts in class 2 with learning using Realistic Mathematics is better than ordinary learning.